2018
DOI: 10.1029/2018sw002080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Version 2 of the International Sunspot Number on Naïve Predictions of Solar Cycle 25

Abstract: The recalibration of the International Sunspot Number brings new challenges to predictions of Solar Cycle 25. One is that the list of extrema for the original series is no longer usable because the values of all maxima and minima are different for the new version of the sunspot number. Timings of extrema are less sensitive to the recalibration but are a natural result of the calculation. Predictions of Solar Cycle 25 published before 2016 must be converted to the new version of the sunspot number. Any predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…The values were clustered near the climatological average rather than the actual, belowaverage, value. Pesnell (2018) found that the climatological predictions of Solar Cycle 24 were less accurate than those in the precursor category. This agrees with Brown (1986) and Li et al (2001), who concluded that methods using a single source of information gave more widely varying predictions for Solar Cycles 21-24.…”
Section: Climatological or Statistical Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…The values were clustered near the climatological average rather than the actual, belowaverage, value. Pesnell (2018) found that the climatological predictions of Solar Cycle 24 were less accurate than those in the precursor category. This agrees with Brown (1986) and Li et al (2001), who concluded that methods using a single source of information gave more widely varying predictions for Solar Cycles 21-24.…”
Section: Climatological or Statistical Methodsmentioning
confidence: 92%
“…The use of a function that resembles a Debye function to represent S can be traced to a Poisson distribution that omitted the c from the denominator (Stewart and Panofsky, 1938;Cook, 1949). It is timely to do this for S as the recalibration changed the shape of several of the double-peaked cycles (Pesnell, 2018). The discrepancy in shape also reduced the agreement between the shape of R Z and F10.7.…”
Section: Theoretical Shape Of Sunspot Number and F107mentioning
confidence: 99%
See 1 more Smart Citation
“…This unusual behavior has drawn the attention of researchers worldwide who have attempted to predict the amplitude of solar cycle 25 (Bhowmik & Nandy, 2018;Cameron et al, 2016;Gopalswamy et al, 2018;Hathaway & Upton, 2016;Iijima et al, 2017;Janardhan et al, 2015;Jiang et al, 2018;Kakad et al, 2017;Kirov et al, 2018;Macario-Rojas et al, 2018;Pesnell & Schatten, 2018;Petrovay et al, 2018;Sarp et al, 2018;Upton & Hathaway, 2014, 2018. The different estimates of SSN in V1.0 and V2.0 for the amplitude of cycle 25 by different researchers along with the ratio of peak SSN of cycle 25 to cycle 24 are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore revisit, in this paper, our earlier prediction in order to update the amplitude of solar cycle 25 using the revised SSN V2.0 observations available after July 2015 and to find out the nature of solar cycle 25. Pesnell (2018) also suggested that the solar cycle 25 predictions which used the SSN V1.0 observations need to be revisited as he showed that the revised SSN V2.0 observations have different values of SSN for the solar maxima and minima compared to the original SSN V1.0 observations. Further, we primarily claimed, in our earlier prediction (JBA15), a possible continuation of a steady declining trend observed in unsigned solar polar fields above latitudes of ≥45°starting from ∼1995 until the minimum of cycle 24.…”
Section: Introductionmentioning
confidence: 99%